The hormonal background of aggression - the role of testosterone and cortisol in the development of violent behaviour (Academic Journal of Internal Affairs, 2025)
hormonal response to stress and influence the functioning of the nervous system at the genetic level, which may have a lasting effect on the organism's behaviour int he future. The so-called dual-hormone hypothesis suggests that the coexistence of high testosterone and low cholesterol is the hormonal basis for the manifestation of aggression, although the link has been shown to be well established in studies of men, and the results for women are incomplete or contradictory.Aim: The article highlights the role of testosterone and cortisol in the hormonal background of aggression. Within the biological causes of violent behaviour, the study of hormonal factors deserves special attention, given that the hormonal system is strongly influenced not only by genetic bases but also by environmental influences.Methodology: This study is based on an analysis and examine of the literature.Findings: In the article, the author points to the differences in testosterone and cortisol levels underlying aggression and the interaction between the two hormones. The interaction of the two hormones under investigation is shown by the so-called dual-hormone hypothesis, for which the studies to date are not entirely clear. Nevertheless, experiments show a tendency to suggest that testosterone and cortisol are not independent of each other but can influence each other's effects.Value: The journal article highlights the importance of the biological, hormonal causes behind aggression and the need for further research on this topic. Research into biological factors is also of particular importance from a legal point of view, as the question of whether the perpetrator has a physiological background that makes him or her only partially responsible for the act of violence or, in some cases, exempt from responsibility, is of importance in assessing the violence.
Keywords: aggression, testosterone, cortisol, dual-hormone hypothesis